2001
DOI: 10.1074/jbc.m103481200
|View full text |Cite|
|
Sign up to set email alerts
|

Hyaluronan Enters Keratinocytes by a Novel Endocytic Route for Catabolism

Abstract: Hyaluronan synthesized in the epidermis has an exceptionally short half-life, indicative of its catabolism by epidermal keratinocytes. An intracellular pool of endogenously synthesized hyaluronan, from 1 to 20 fg/cell, inversely related to cell density, was observed in cultured rat epidermal keratinocytes. More than 80% of the intracellular hyaluronan was small (<90 kDa). Approximately 25% of newly synthesized hyaluronan was endocytosed by the keratinocytes and had a half-life of 2-3 h. A biotinylated aggrecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(196 citation statements)
references
References 67 publications
16
173
4
1
Order By: Relevance
“…The cell-associated fraction did contain a smaller peak of lower-M W HA consistent with a pool of intracellular, partially degraded HA as previously reported (28). After addition of BMP7-, an increase in the amount of radiolabeled HA was seen in the supernatant (CM fraction), the pericellular protein bound PC fractions, and the cell-associated (CA) fractions.…”
Section: Characterization Of Ha After Bmp7 or Il-1 Stimulationmentioning
confidence: 51%
“…The cell-associated fraction did contain a smaller peak of lower-M W HA consistent with a pool of intracellular, partially degraded HA as previously reported (28). After addition of BMP7-, an increase in the amount of radiolabeled HA was seen in the supernatant (CM fraction), the pericellular protein bound PC fractions, and the cell-associated (CA) fractions.…”
Section: Characterization Of Ha After Bmp7 or Il-1 Stimulationmentioning
confidence: 51%
“…Techniques for measuring and analyzing FRET signals in living cells have been reported [22]. Previous investigations have indicated that exogenous HA is transported to the endosomal/ lysosomal system for degradation [23]. Thus, the FRET-HA substrate may be a new tool for investigating hyaluronidase activity in intact living cells.…”
Section: Discussionmentioning
confidence: 99%
“…96 EM imaging studies and inhibition of cell entry by multiple inhibitors led the authors to conclude that magnetofectins entered cells through both clathrin-and caveolae-mediated pathways. Endocytic cell entry was inhibited by nystatin, which blocks caveolae formation, 97,98 and antimycin A, which generally depletes ATP, indicating that uptake occurred by energy-dependent endocytosis. Transfection was also inhibited by chloroquine, suggesting that complexes were trapped in early endosomes, and required acidification to facilitate endosomal release.…”
Section: Intracellular Trafficking Of Nonviral Vectors Lk Medina-kauwmentioning
confidence: 99%